Consumindo moda, estilos e individualidades : um estudo etnográfico das práticas de consumo de moda em grupos populares - Appel, Polyanna Brandão (2013)
This work proposes to understand how is the fashion consumption by the popular groups, since these individuals come to enjoy easy access to information, and consumer credit. The general objective this study is to perceive that forms these individuals are fashion consuming - how to manipulate the fashion codes, if the choices of clothing are or are not linked to the social context as they are inserted, maneuvers that are evidenced in these social practices, in sum, what it see through the appropriations given to the fashion consumption in this social group. The survey was constructed from the ethnographic method, and participative observation as its main instrument. Also, are used pictures of who live, collected on their personal pages on the Facebook site, intending to exemplify and demonstrate their practices. Thus, putting fashion as consumption practices, and from it, was thought about a process of style constructing and also individualization